Manufacturing Strategy / The Strategic Management of the Manufacturing Function Second Edition - Hill Terry; Macmillan Company (1993)
This book shows that a strategic approach to manufacturing management is essential for the survival and prosperity of industrial companies. International Comparisons, Manufacturing Implications of Corporate Marketing Decisions, Order-winners and Qualifiers, Choice of Process, Focused Manufacturing, Process Positioning, Manufacturing Infrastructure Development, Accounting and Financial Perspectives and Manufacturing Strategy.